The effect of bio- and mineral fertilizers on corn grain yield - Yeremko, L.; Kyrlytsia, A. (Scientific Progress & Innovations, 2025)
An effective way to stabilize corn production, an important crop with universal use, is to optimize plant nutrition through a combination of biological and mineral fertilizers. A field experiment to study the effect of different levels of mineral fertilization and pre-sowing seed treatment with Bio-Mineralis biofertilizer (3.0 L t-1) on the yield of the mid-season corn hybrid DN Demeter (FAO 300) was conducted in 2022–2024 at the experimental field of the Poltava State Agricultural Experimental Station named after M.I. Vavilov of the Institute of Pig Breeding and Agro-Industrial Production of the National Academy of Agrarian Sciences. The aim of the study was to determine the effect of different levels of mineral fertilizer and the use of biofertilizer on corn yield formation. The experiment showed that improving the nutritional status of plants by the use of mineral fertilizers, seed treatment with biofertilizer and their combination had a positive effect on the growth, development, and formation of corn productivity elements. This was confirmed by an increase in leaf surface area compared with the control. The most effective was the variant with the combined use of biofertilizers and mineral fertilizers – in this case, the leaf surface indicators were the highest. As a result of the formation of a more developed leaf surface and increased productivity of photosynthetic activity of plants, an increase in plant weight in a completely dry state was observed. This was most evident in the variant with the use of Bio-Mineralis in combination with N70P60K80. Increasing the intensity of organic matter synthesis contributed to their better supply to ears and grains during filling, which resulted in grain yield increase. The highest yield – 8.21 t ha-1 – was obtained in the variant with pre-sowing seed treatment with Bio-mineralis biofertilizer and N70P60K80 application. The increase in yield due to the use of mineral fertilizers was 11.8–15.2 %, and the seed treatment with biofertilizer contributed to an increase in grain productivity by 1.8 %.